PERISTALTIC TRANSPORT OF A MAGNETIC FLUID THROUGH POROUS MEDIA IN A UNIFORM AND NON-UNIFORM ANNULUS - S.K., Asha (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
The aim of the present investigation is to study the peristaltic transport through the gap between coaxial tubes, where the outer tube is non uniform and the inner tube is rigid. The necessary theoretical results such as viscosity, pressure gradient and friction force on the inner and outer tubes have been obtained in terms of couple stress parameter. Out of these theoretical results the numerical solution of pressure gradient, outer friction, inert friction and flow rate are shown graphically for the better understanding of the problem. Â Keyword: Peristaltic transport, Magnetic fluid, porous media.